Model-Driven Development and Operation of Multi-Cloud Applications The MODAClouds Approach - Di Nitto, Elisabetta; Matthews, Peter; Petcu, Dana; Solberg, Arnor (SpringerBriefs in Applied Sciences and Technology, 2017)
This book is open access under a CC BY 4.0 license.